2017
DOI: 10.1159/000480633
|View full text |Cite
|
Sign up to set email alerts
|

Early Nutrition and Growth until the Corrected Age of 2 Years in Extremely Preterm Infants

Abstract: Background: Extremely preterm birth is associated with a high risk of extrauterine growth retardation, which has been linked with adverse developmental outcomes. Objective: We investigated whether nutritional management during the first 7 days of life affects growth patterns until the corrected age of 2 years in extremely preterm infants. Study Design: A retrospective study of 78 extremely preterm (<28 weeks' gestation) neonates was conducted. Data regarding parenteral and enteral intake of energy, protein, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
(32 reference statements)
0
22
0
2
Order By: Relevance
“…Improvements in neonatal care and more aggressive nutritional strategies have aimed to promote postnatal growth (32,33) and improve neurodevelopment outcomes (33)(34)(35). However, these nutritional interventions might also be associated with other adverse health consequences (7).…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in neonatal care and more aggressive nutritional strategies have aimed to promote postnatal growth (32,33) and improve neurodevelopment outcomes (33)(34)(35). However, these nutritional interventions might also be associated with other adverse health consequences (7).…”
Section: Discussionmentioning
confidence: 99%
“…Optimal early nutrition in preterm infants has been associated with better growth and neurodevelopmental outcomes. The total energy intake during the first 7 days of life is positively correlated with improved growth parameters until the corrected age of 2 years [1]. Coviello et al found a positive relationship between the initial 4 weeks of nutrition, with neurodevelopment, and white matter maturation at term equivalent age (TEA) in preterm infants < 31 weeks of gestation [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this model, we considered some conditions that could affect infant growth. Previous studies in similar setting do not report R-squared values [21,[26][27][28][29]. Bonsante et al reported R-squared value of their linear regression analysis [7].…”
Section: Plos Onementioning
confidence: 92%
“…were due to protein or energy intake [25][26][27]. Unlike previous trials, our study was designed to assess the effects on long-term growth of two PN protocols, different for energy intakes but similar for protein intakes.…”
Section: Plos Onementioning
confidence: 99%